Breakdown maintenance process / Wan Lut Fasihah Fitri Marni Wan Mohamad - Wan Mohamad, Wan Lut Fasihah Fitri Marni (2016)
The training program industry is one of the program was designed to give a true picture of the working environment for the student. Thus, the student were required to write daily report in the logbook and provide a full report to be presented to the lecturers as evidence that student has completed industry training program as required. I has chosen the prokel management sdn bhd. (PMSB) as a place for my training industry. The knowledge that I have been able during training industry, I was taught the process of breakdown maintenance and how to manage the paper work during do a company work. All the knowledge I acquired during training industry had I explain in detail in the book of daily report.